2020
DOI: 10.3390/jpm11010013
|View full text |Cite
|
Sign up to set email alerts
|

Gallstone Disease, Obesity and the Firmicutes/Bacteroidetes Ratio as a Possible Biomarker of Gut Dysbiosis

Abstract: Obesity is a major risk factor for developing gallstone disease (GSD). Previous studies have shown that obesity is associated with an elevated Firmicutes/Bacteroidetes ratio in the gut microbiota. These findings suggest that the development of GSD may be related to gut dysbiosis. This review presents and summarizes the recent findings of studies on the gut microbiota in patients with GSD. Most of the studies on the gut microbiota in patients with GSD have shown a significant increase in the phyla Firmicutes (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(119 citation statements)
references
References 151 publications
12
101
0
6
Order By: Relevance
“…The FMRP treatment significantly (p < 0.05) recovered the Firmicute/Bacteroidetes ratio in the DB group. The relative abundance of microbial composition in metabolic disorder and IBD was compatible with previous research [47,48]. Bacteroidetes is mainly associated with healthy gut microbiota composition [49].…”
Section: Discussionsupporting
confidence: 88%
“…The FMRP treatment significantly (p < 0.05) recovered the Firmicute/Bacteroidetes ratio in the DB group. The relative abundance of microbial composition in metabolic disorder and IBD was compatible with previous research [47,48]. Bacteroidetes is mainly associated with healthy gut microbiota composition [49].…”
Section: Discussionsupporting
confidence: 88%
“…Such findings strongly suggest the importance of including microbiomes into the framework of precision medicine. Although the pathogenesis of cholesterol gallstones is still not fully understood, gut microbiota dysbiosis plays an important role in their formation [14]. There is a paucity of studies describing fecal/gut bacteriobiome profiles in GSD-afflicted patients, both before and after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 16s rRNA sequencing revealed that the abundance, richness, and diversity of colonic microbiota were decreased in the jet-lagged mice. Moreover, induction of jet lag increased the F:B ratio, an indicator for the imbalance of gut microbiota (De Luca and Shoenfeld, 2019;Crovesy et al, 2020;Grigor'eva, 2020;Stojanov et al, 2020). Studies have shown that obese animals and humans had a higher F:B ratio compared with normal weight individuals (Magne et al, 2020).…”
Section: Discussionmentioning
confidence: 99%